Method for controlling brittle inclusions in steel cord

By controlling the chemical composition and smelting process of the wire rope, the fracture problem caused by brittle inclusions in the manufacturing and processing of the wire rope is solved, and the production of wire rope with thin diameter, high strength and long life is achieved.

JP2025504469AActive Publication Date: 2025-02-12ZHANGJIAGANG RONGSHENG SPECIAL STEEL CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024543090
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-10
Filing Date
2022-07-12
Publication Date
2025-02-12
Estimated Expiration
2042-07-12

AI Technical Summary

Technical Problem

During the manufacturing and processing of existing wire ropes, they are susceptible to brittle inclusions such as Al2O3, MgO·Al2O3, which leads to fracture problems and cannot meet the needs of thin diameter, high strength and long life.

Method used

By controlling the chemical composition and smelting process of the wire rope, including adding low-nitrogen carbonate and silicon carbides to the steel liquid, adjusting the chemical composition and temperature in the furnace, combining specific refractory materials and process parameters, reducing the generation and erosion of brittle inclusions, and improving the purity and strength of the wire rope.

Benefits of technology

The generation of brittle inclusions such as Al2O3, MgO·Al2O3 is significantly reduced, the breakage rate of the wire rope is reduced, the manufacturing and processing quality of the wire rope is improved, and the requirements of thin diameter, high strength and long life are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504469000001_ABST
    Figure 2025504469000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for controlling brittle inclusions in steel cord, in which an alloy is added in a primary smelting and tapping process in a furnace, silicon carbide and synthetic slag are added to the slag surface of the ladle after tapping is completed to produce slag, an alloy is added in a refining process, carbon wire is introduced, lime, silicon carbide and synthetic slag are added and the slag is melted by passing an electric current through it, and the slag components satisfy CaO / SiO2=0.9-1.2, Al2O3≦5%, MgO 4-8%, and [MnO+T.Fe] 2-5%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of steel smelting, and more particularly to a method for controlling brittle inclusions in steel cord. [Background technology]

[0002] Currently, steel cord is mainly used in the industry to be drawn into fine wires, generally drawn into fine wires with diameters of 0.12 to 0.35 mm, and when used as saw wires, they must be drawn into diameters of 0.12 mm or less. Saw wires, also called cutting wires, cutting steel wires, or cutting wires, are special wires for splitting, and are widely used as consumer materials in the fields of energy, aviation, equipment, and public facilities, such as cutting and shaping solar cell silicon wafers, quartz materials, single crystal silicon, and polycrystalline silicon. Diamond particles can also be embedded in the saw wire to produce diamond saw wires, also called diamond cut wires, diamond cutting wires, and diamond wires.

[0003] In order to reduce losses during the cutting process of materials such as silicon, the performance of saw wire must be finer in diameter, longer in length without breakage, and stronger. However, the steel cords currently manufactured in the industry are affected by inclusions in the steel material. In particular, brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) are very likely to cause breakage problems during the manufacturing, processing, and use of steel cords. Therefore, when existing steel cords are used as saw wires, their performance cannot meet market needs. As shown in Figures 1 to 4, Figure 1 shows the distribution of inclusions in a steel cord manufactured by a conventional manufacturing process in a SiO2-MnO-Al2O3 ternary phase diagram, Figure 2 shows the morphology of the fine wire fracture surface due to Al2O3 inclusions in the wire core part of a steel cord manufactured by a conventional manufacturing process, Figure 3 shows the morphology of the fine wire fracture surface due to Al2O3 inclusions in the wire edge part of a steel cord manufactured by a conventional manufacturing process, and Figure 4 shows the morphology of the fine wire fracture surface due to magnesia-alumina spinel (MgO·Al2O3) inclusions in the wire core part of a steel cord manufactured by a conventional manufacturing process. Summary of the Invention

[0004] In order to solve at least one of the above technical problems, an object of the present invention is to provide a method for controlling brittle inclusions in a steel cord.

[0005] In order to achieve one of the above objects, one embodiment of the present invention provides a method for controlling brittle inclusions in a steel cord, the method comprising the steps of: C 0.70-0.95%, Si 0.15-0.45%, Mn 0.25-0.80%, Cr 0.10-0.45%, P≦0.015%, S≦0.01%, Alt≦0.0008%, N≦0.003%, O≦0.002%, with the balance being Fe and other unavoidable impurities, comprising: The primary smelting process in the furnace involves deoxidizing and alloying the molten steel, laying 0.5-1 kg / t of silicon carbide and 40-60% low-nitrogen carburizer at the bottom of the ladle that receives the molten steel before tapping, gradually adding alloys during tapping, adding all of the alloys by the time the steel reaches 75% and starting to add the remaining 40-60% low-nitrogen carburizer at a rate of 200-300 kg / min when the steel reaches 80%. After the low-nitrogen carburizer has completely dissolved in the molten steel, tapping is stopped and 0.5-1 kg / t of silicon carbide is added to the slag surface of the ladle and 3-5 kg / t of synthetic slag is added to create slag. The molten steel that has undergone primary smelting in the furnace is transferred to the LF furnace and refined to obtain the following components by mass percentage: C 0.70-0.95%, Si 0.15-0.45%, Mn 0.25-0.80%, Cr In order to adjust the chemical composition of the molten steel to satisfy the following, the temperature, chemical composition and contents of the molten steel are detected, and the above-mentioned alloy is added according to the detected chemical composition and contents of the molten steel, and a carbon wire is inserted, and lime, silicon carbide and synthetic slag are added and the slag is melted by passing an electric current through the molten steel. The temperature of the molten steel is adjusted to 1510-1535°C, and the slag composition is, in mass percent, CaO / SiO2=0.9-1.2, Al2O3≦5%, MgO 4-8%, [MnO+T.Fe] A refining process in which the content of molten steel is 2-5%, with the remainder being other unavoidable impurities, and then the ladle bottom blowing is adjusted to a soft stirring mode, the soft stirring time is set to >20 min, and steel is tapped; a billet casting process in which the molten steel tapped in the refining process is transferred to a continuous casting platform and left to stand for 15 minutes or more, a stopper sand is introduced into a slag receiver when pouring into a large ladle, and the molten steel is protectively poured into a tundish to form a continuous cast billet, in this order; The alloy contains ferrosilicon, metallic manganese and ferrochromium, the ferrosilicon contains Al≦0.035%, the metallic manganese contains Al≦0.015%, the ferrochromium contains Al≦0.020% and C≦0.15%, and the low-nitrogen carburizer contains N≦0.015%.

[0006] By controlling the chemical composition and mass percentage of the steel cord, and further laying silicon carbide and low-nitrogen carburizers in advance at the bottom of the ladle before tapping in the primary smelting process in the furnace, the boiling of molten steel is made gentle by adding low-nitrogen carburizers to the bottom of the ladle at the beginning of tapping, and the amount of low-nitrogen carburizers added during the tapping process in the primary smelting process is significantly reduced, and a large amount of low-nitrogen carburizer floating on the slag surface and causing a carbon-oxygen reaction on the slag surface to generate a large amount of gas and cause splashes is avoided, and thus the flow rate of the bottom blowing of the ladle during tapping and The use of silicon carbide instead of calcium carbide can not only reduce the amount of molten steel lost due to deoxidation, but also reduce the cost of alloying. The use of silicon carbide instead of calcium carbide can quickly deoxidize the steel, reduce the amount of molten steel in the ladle at the beginning of tapping, and increase the clearance of the ladle. In this case, not only will the splash of molten steel caused by deoxidation boiling not be caused, but the generated SiO2 will help to keep the slag basicity of the ladle low. In addition, by increasing the carbon powder with carbon wire in the refining process and immediately adding the carbon powder to the molten steel, the use of bottom blowing can be avoided, reducing the erosion of refractory materials and reducing the generation of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) can be reduced. The addition of lime and synthetic slag immediately after adjusting the chemical composition of the molten steel can increase the slag basicity and contribute to the adsorption of Al2O3 and SiO2 inclusions. Furthermore, in the billet casting process, by introducing stopper sand into the slag receiver during pouring, it is possible to prevent the stopper sand from being mixed into the molten steel and increasing the amount of Al2O3 inclusions in the molten steel. Furthermore, by controlling the Al content in the alloy, it is possible to reduce the amount of Al2O3 inclusions and SiO2-MnO-Al2O3 composite inclusions in the molten steel. The above control method not only reduces the erosion of the refractory material, but also reduces the amount of acid-soluble aluminum Als in the molten steel, reduces the amount of Al2O3 precipitated during the billet casting process, effectively controls brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) in the steel cord, and reduces the breakage rate during the manufacturing, processing, and use of the steel cord.

[0007] As a further improvement of one embodiment of the present invention, the bottom bricks, molten pool bricks and ladle mouth bricks of the ladle are all made of magnesia carbon bricks, and the magnesia carbon bricks have an Al2O3≦3%. The slag line bricks and breathable bricks of the ladle are made of magnesium-zirconium-carbon bricks, and the Al2O3≦3%. The long nozzle of the ladle is made of corundum long nozzle, and the inner wall of the long nozzle is coated with a SiO2 coating, and the thickness of the SiO2 coating is 3-8 mm. By limiting the materials of refractory materials such as the ladle bottom bricks, molten pool bricks, ladle mouth bricks, slag line bricks, permeable bricks and long nozzle and controlling the Al2O3 content therein, and coating an SiO2 coating on the inner wall of the long nozzle, the SiO2 coating, which has a high melting point, can withstand molten steel with a pouring temperature of 1500-1520°C, and reduces the risk of Al2O3 inclusions being formed due to the erosion of the long nozzle of a large ladle being mixed into molten steel, thereby reducing the erosion of the ladle refractory materials during steelmaking and reducing the amount of Al2O3 and MgO mixed into molten steel, which in turn significantly reduces the occurrence of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) in the final steel cord produced, and further improving the stability of the production quality of the steel cord.

[0008] In a further improvement of one embodiment of the present invention, the stopping sand is silicon-chromium stopping sand, in which Al2O3≦5%, which can prevent the stopping sand from flowing into the tundish together with the molten steel during pouring, resulting in an excessive amount of excess Al2O3 in the molten steel, and can reduce the occurrence of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) in the final steel cord.

[0009] In a further improvement of the embodiment of the present invention, a magnesium coating is applied to the inner wall of the tundish, and Al2O3≦2% in the magnesium coating, a magnesium-zirconium-carbon weir is used for the weir of the tundish, and Al2O3≦5% in the magnesium-zirconium-carbon weir is used for the weir of the tundish, and a magnesia carbon nozzle is used for both the upper nozzle and the submerged nozzle of the tundish, and Al2O3≦5% in the magnesia carbon nozzle is used for both the upper nozzle and the submerged nozzle. By limiting the material of the tundish and controlling the Al2O3 content therein, it is possible to reduce the erosion of the tundish refractory material during the steelmaking process, reduce the amount of Al2O3 and MgO mixed into the molten steel, and thereby greatly reduce the occurrence of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) in the finally manufactured steel cord.

[0010] As a further improvement of one embodiment of the present invention, in the in-furnace primary smelting step, smelting is performed in a converter or an electric furnace, and the molten steel temperature at the end of smelting is ≧1650° C., C≧0.10%, and O≦0.03%. By tapping steel at high carbon, low oxygen, and high temperature in the in-furnace primary smelting step, the reaction strength between the molten steel and the low-nitrogen carburizer pre-placed in the ladle can be reduced, and the molten steel can be quickly deoxidized by the silicon carbide pre-placed in the ladle, thereby reducing the boiling degree of the molten steel and avoiding splashing of the molten steel.

[0011] As a further improvement of one embodiment of the present invention, in the primary smelting process in the furnace, the ladle bottom blowing flow rate is 100 to 200 NL / min at the beginning of tapping and during the alloying process, the ladle bottom blowing flow rate is 600 to 800 NL / min when the remaining 40 to 60% of the low nitrogen carburizer is started to be added when 80% of the steel is tapped, and the ladle bottom blowing flow rate is 300 to 500 NL / min when silicon carbide and synthetic slag are added to the slag surface of the ladle to create slag after tapping is completed. By increasing the flow rate of the bottom blowing of the ladle during the process of adding the remaining 40 to 60% of the low-nitrogen carburizer, the low-nitrogen carburizer is entrained in the molten steel. On the other hand, by using medium to low flow rates of bottom blowing at the initial stage of tapping, the alloying process, and the slag making process, the stirring intensity of the molten steel is reduced, slag entrainment is avoided, erosion of the refractory material is reduced, loss of refractory material is reduced, the cleanliness of the molten steel is improved, and the formation of large amounts of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) in the molten steel is prevented, and further breakage of the wire during drawing due to their penetration into the wire rod for further processing is avoided.

[0012] As a further improvement of one embodiment of the present invention, in the refining process, the ladle bottom blowing flow rate is 100-150NL / min in the process of detecting the molten steel temperature, chemical components and their contents, the ladle bottom blowing flow rate is 300-400NL / min in the process of adding the alloy and introducing the carbon wire, the ladle bottom blowing flow rate is 200-300NL / min in the process of melting the slag by applying current, and the ladle bottom blowing flow rate is 30-80NL / min in the soft stirring process. By using a medium to low flow rate bottom blowing throughout the entire refining process, the stirring intensity of the molten steel is reduced, slag entrainment is avoided, erosion of the refractory material is reduced, loss of the refractory material is reduced, the cleanliness of the molten steel is improved, and the formation of a large amount of brittle inclusions such as Al2O3, magnesia-alumina spinel (MgO·Al2O3) in the molten steel is avoided, and frequent wire breakage during drawing for further processing due to the intrusion of the inclusions into the wire is avoided.

[0013] As a further improvement of one embodiment of the present invention, from the end of tapping in the primary smelting process in the furnace to the end of adjusting the chemical composition of the molten steel in the refining process, the slag basicity of the ladle is ≦0.6, and in the refining process, 1-2 kg / t of lime, 1-1.5 kg / t of silicon carbide, and 8-15 kg / t of synthetic slag are added so that the slag basicity of the ladle is 0.9-1.2. By not adding lime during the tapping process in the primary smelting process in the furnace, and only adding a small amount of low-basicity synthetic slag, the low slag basicity of the ladle is guaranteed, and the oxidizing properties of the molten steel and slag are low, the molten aluminum in the molten steel is reduced to an extremely low level, and the precipitation of Al2O3 inclusions in the continuous casting process can be reduced, and the Al in the alloy can be oxidized to Al2O3 and floated on the slag to be separated from the molten steel, and the amount of slag is small, which, combined with the low bottom blowing flow rate of the ladle, significantly reduces the erosion of the ladle refractory material. It can weaken the molten steel composition and further reduce the formation of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3). In the refining process, adding lime and synthetic slag immediately after accurately adjusting the molten steel composition to increase the slag basicity to 0.9-1.2 helps to adsorb Al2O3 inclusions and SiO2 acidic inclusions. In addition, such a low slag basicity in the refining process can reduce the bottom blowing flow rate of the ladle to less than 50% of the normal bottom blowing flow rate, greatly reducing the bottom blowing flow rate and further reducing the erosion of the ladle refractory material.

[0014] As a further improvement of one embodiment of the present invention, the chemical composition of the silicon carbide includes, by mass percent, SiC≧99.3%, and other inevitable impurities, and the chemical composition of the synthetic slag includes, by mass percent, CaO 35-45%, SiO2 45-55%, MgO 3-8%, Al2O3≦2%, and other inevitable impurities. The high purity silicon carbide can not only realize rapid deoxidation, but also can moderate the boiling of molten steel by the low nitrogen recarburizer laid at the bottom of the ladle, and the limited chemical composition and content of the synthetic slag can ensure the low basicity of the synthetic slag, which can reduce the flow rate of the bottom blowing of the ladle and further reduce the erosion of the ladle refractory material.

[0015] As a further improvement of one embodiment of the present invention, in the billet casting step, Als in the molten steel in the tundish is ≦0.0005%, the content of Al2O3 inclusions in the molten steel is ≦10%, the size of Al2O3 inclusions and magnesia-alumina spinel inclusions is <5 μm, and the density of Al2O3 inclusions and magnesia-alumina spinel inclusions with a size of 1 to 5 μm is ≦0.0005 pieces / mm 2 By controlling the content of acid-soluble aluminum Als in molten steel, it is possible to reduce the amount of Al2O3 precipitated during the continuous casting process, thereby reducing the content, size and density of brittle inclusions such as Al2O3 inclusions and magnesia-alumina spinel inclusions in the finally manufactured steel cord, thereby improving the cleanliness of the steel cord and decreasing the breakage rate. [Brief description of the drawings]

[0016] [Figure 1] The distribution of inclusions in a steel cord produced by a conventional manufacturing process is shown in a ternary phase diagram of the SiO2-MnO-Al2O3 system. [Diagram 2] The figure shows the morphology of the fracture surface of a thin wire caused by Al2O3 inclusions in the wire core of a steel cord manufactured by a conventional manufacturing process. [Diagram 3] The figure shows the morphology of the cross section of a thin wire fractured due to Al2O3 inclusions at the edge of the wire in a steel cord manufactured by a conventional manufacturing process. [Figure 4] The morphology of the fracture surface of thin wire caused by magnesia-alumina spinel (MgO·Al2O3) inclusions in the wire core of a steel cord manufactured by a conventional manufacturing process is shown. [Diagram 5] 1 shows a distribution state of inclusions in a steel cord according to one embodiment of the present invention in a SiO2-MnO-Al2O3 ternary phase diagram. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] One embodiment of the present invention provides a method for controlling brittle inclusions in a steel cord, the chemical composition of the steel cord comprising, in mass percent, 0.70-0.95% C, 0.15-0.45% Si, 0.25-0.80% Mn, 0.10-0.45% Cr, P≦0.015%, S≦0.01%, Alt≦0.0008%, N≦0.003%, O≦0.002%, and the balance being Fe and other unavoidable impurities.

[0018] The method for controlling brittle inclusions in a steel cord according to the present invention has been obtained based on many experiments and researches. The method for controlling brittle inclusions in a steel cord will be further described below with reference to specific examples.

[0019] The method for controlling brittle inclusions in a steel cord includes the following steps (1), (2), and (3) in this order.

[0020] (1) Primary smelting process in the furnace Smelting is carried out in a converter or electric furnace, the molten steel is deoxidized and alloyed, the molten steel temperature at the end of smelting is ≧1650℃, C≧0.10%, O≦0.03%, the slag is stopped at the end of smelting and the steel is tapped, before the steel is tapped, 0.5~1kg / t of silicon carbide and 40~60% of low nitrogen carburizer are laid at the bottom of the ladle receiving the molten steel, and the alloy is added successively during the tapping to alloy it, all the alloy is added by the time the steel is 75%, and when the steel is 80%, the remaining 40~60% of the low nitrogen carburizer begins to be added at a rate of 200~300kg / min, after the low nitrogen carburizer is completely dissolved in the molten steel, the steel is stopped and 0.5~1kg / t of silicon carbide is added to the slag surface of the ladle, and 3~5kg / t of synthetic slag is added to make the slag.

[0021] Preferably, the alloy comprises ferrosilicon, manganese metal and ferrochromium, wherein Al≦0.035% in the ferrosilicon, Al≦0.015% in the manganese metal, Al≦0.020% and C≦0.15% in the ferrochromium, and N≦0.015% in the low nitrogen carburizer.

[0022] Preferably, the bottom bricks, molten pool bricks and ladle mouth bricks of the ladle are all made of magnesia carbon bricks, and the magnesia carbon bricks have an Al2O3≦3%. The slag line bricks and breathable bricks of the ladle are made of magnesium-zirconium-carbon bricks, and the Al2O3≦3%. The long nozzle of the ladle is a corundum long nozzle, and an SiO2 coating is applied to the inner wall of the long nozzle, and the thickness of the SiO2 coating is 3-8 mm.

[0023] More preferably, the upper limit of the number of times the ladle bottom bricks, molten pool bricks and ladle mouth bricks can be used is set to 35 to 45 times, and the upper limit of the number of times the ladle slag line bricks and permeable bricks can be used is set to 15 to 25 times. In this way, the quality stability of the refractory material of the ladle can be guaranteed, and it is possible to avoid a situation in which the erosion of the refractory material of the ladle becomes increasingly severe with the passage of time of use, causing a large amount of Al2O3 and MgO in the refractory material of the ladle to be mixed into molten steel, resulting in an excessive increase in brittle inclusions such as Al2O3 inclusions and magnesia-alumina spinel inclusions in the finally manufactured steel cord.

[0024] Preferably, the ladle bottom blowing flow rate is 100 to 200 NL / min at the beginning of tapping and during the alloying process, the ladle bottom blowing flow rate is 600 to 800 NL / min when the remaining 40 to 60% of the low nitrogen carburizer is added after 80% of the steel is tapped, and the ladle bottom blowing flow rate is 300 to 500 NL / min when silicon carbide and synthetic slag are added to the slag surface of the ladle to create slag after tapping is completed.

[0025] Preferably, the chemical composition of the silicon carbide includes, in mass percent, SiC≧99.3%, and other unavoidable impurities, and the chemical composition of the synthetic slag includes, in mass percent, CaO 35-45%, SiO2 45-55%, MgO 3-8%, Al2O3≦2%, and other unavoidable impurities.

[0026] (2) Refining process The molten steel that has undergone primary smelting in the furnace is transferred to the LF furnace and refined to obtain the following components by mass percentage: C 0.70-0.95%, Si 0.15-0.45%, Mn 0.25-0.80%, Cr In order to adjust the chemical composition of the molten steel so that it satisfies the following composition by mass: CaO / SiO2=0.9-1.2, Al2O3≦5%, MgO 4-8%, [MnO+T.Fe] 2-5%, and the balance being other unavoidable impurities, the temperature, chemical composition and contents of the molten steel are detected, and the above-mentioned alloys are added according to the detected chemical composition and contents of the molten steel, carbon wire is introduced, lime, silicon carbide and synthetic slag are added and electric current is passed through to melt the slag, the temperature of the molten steel is adjusted to 1510-1535°C, and the slag composition satisfies the following composition by mass: CaO / SiO2=0.9-1.2, Al2O3≦5%, MgO 4-8%, [MnO+T.Fe] 2-5%, and the balance being other unavoidable impurities, and then the ladle bottom blowing is adjusted to the soft stirring mode, the soft stirring time is set to >20 min, and the steel is tapped.

[0027] Here, [MnO+T.Fe] represents the sum of the mass percentages of MnO and T.Fe.

[0028] Preferably, in the process of detecting the molten steel temperature, chemical components and their contents, the ladle bottom blowing flow rate is 100 to 150 NL / min, in the process of adding the alloy and introducing the carbon wire, the ladle bottom blowing flow rate is 300 to 400 NL / min, in the process of melting the slag by passing current, the ladle bottom blowing flow rate is 200 to 300 NL / min, and in the soft stirring process, the ladle bottom blowing flow rate is 30 to 80 NL / min.

[0029] Preferably, the slag basicity in the ladle is kept at 0.6 or less from the end of tapping in the in-furnace primary smelting step until the end of adjustment of the chemical components of the molten steel in the refining step.

[0030] Preferably, in the refining step, 1 to 2 kg / t of lime, 1 to 1.5 kg / t of silicon carbide, and 8 to 15 kg / t of synthetic slag are added so that the slag basicity in the ladle is 0.9 to 1.2.

[0031] Preferably, the chemical composition of the silicon carbide includes, in mass percent, SiC≧99.3%, and other unavoidable impurities, and the chemical composition of the synthetic slag includes, in mass percent, CaO 35-45%, SiO2 45-55%, MgO 3-8%, Al2O3≦2%, and other unavoidable impurities.

[0032] (3) Billet casting process The molten steel tapped in the refining process is transferred to the continuous casting platform and left to stand for more than 15 minutes. When pouring into the large ladle, blocking sand is introduced into the slag receiver, and the molten steel is poured protectively into the tundish to form a continuous cast billet.

[0033] Preferably, the stopping sand is silicon chrome stopping sand, in which Al2O3 is ≦5%.

[0034] Preferably, a magnesium coating is applied to the inner wall of the tundish, and Al2O3 in the magnesium coating is ≦2%, a magnesium-zirconium-carbon weir is used for the weir of the tundish, and Al2O3 in the magnesium-zirconium-carbon weir is ≦5%, and a magnesia carbon nozzle is used for both the upper nozzle and the submerged nozzle of the tundish, and Al2O3 in the magnesia carbon nozzle is ≦5%.

[0035] The results showed that the acid-soluble aluminum Als in the molten steel of the tundish was ≦0.0005%, the content of Al2O3 inclusions in the inclusions of the molten steel was ≦10%, the size of Al2O3 inclusions and magnesia-alumina spinel inclusions was <5μm, and the density of Al2O3 inclusions and magnesia-alumina spinel inclusions with sizes of 1~5μm was ≦0.0005 pieces / mm 2 It is.

[0036] In order to clarify the objectives, technical solutions and advantages of one embodiment of the present invention, the method for controlling brittle inclusions in a steel cord of the present embodiment will be further described below by Examples 1 and 2 according to one embodiment of the present invention. Obviously, Examples 1 and 2 described are only a part of the examples of the present invention, but not all of the examples.

[0037] Example 1 (1) Primary smelting process in the furnace Smelting was carried out in a 135 t converter. Table 1 shows the molten steel temperature, C content, and O content at the end of smelting in the converters (1) to (4). [Table 1]

[0038] At the end of smelting, slag was stopped and steel was tapped. Before tapping, silicon carbide and 40-60% low nitrogen carburizer were laid in advance at the bottom of the ladle receiving the molten steel. Alloys were added sequentially during tapping to alloy the steel. All alloys were added by the time the steel reached 75%. When the steel reached 80%, the remaining 40-60% low nitrogen carburizer was added at a rate of 200-300 kg / min. After the low nitrogen carburizer was completely dissolved in the molten steel, tapping was stopped and silicon carbide was added to the slag surface of the ladle. Synthetic slag was added to make slag, and the slag basicity of the ladle was ≦0.6. The amounts of silicon carbide laid at the bottom of the ladle, silicon carbide added to the slag surface of the ladle after tapping, and synthetic slag added in the converters with furnace numbers (1) to (4) are shown in Table 2. [Table 2]

[0039] Bottom blowing was performed throughout the entire tapping process. Table 3 shows the flow rates of bottom blowing for converters (1) to (4) at the beginning of tapping, during the alloying process, when 80% of the steel is tapped and the addition of the remaining 40 to 60% low-nitrogen carburizer begins, and when tapping is completed and silicon carbide and synthetic slag are added to the slag surface of the ladle to make slag. [Table 3]

[0040] (2) Refining process The molten steel that has undergone primary smelting in the furnace is transferred to the LF furnace for refining, and the chemical composition of the molten steel is, in mass percent, C 0.70-0.95%, Si 0.15-0.45%, Mn 0.25-0.80%, Cr 0.10-0.45%, P 0.007-0.015%, S 0.006-0.01%, Alt 0.0005-0.0008%, N 0.0015-0.0030%, O In order to satisfy the following conditions, the temperature, chemical composition and content of the molten steel were detected, the above alloy was added according to the detected chemical composition and content of the molten steel, carbon wire was inserted, lime, silicon carbide and synthetic slag were added, and the slag was melted by applying electricity, the temperature of the molten steel was adjusted to 1510-1535°C, and the slag components were adjusted to satisfy the following conditions in mass percent: CaO / SiO2=0.9-1.2, Al2O3≦5%, MgO 4-8%, [MnO+T.Fe] 2-5%, and the balance was other unavoidable impurities, and then the ladle bottom blowing was adjusted to the soft stirring mode, the soft stirring time was set to >20min, and the steel was tapped. The amounts of lime, silicon carbide and synthetic slag added to the LF furnaces with furnace numbers (1)-(4) and the slag basicity of the slag in the ladle are shown in Table 4. [Table 4]

[0041] Table 5 shows the ladle bottom blowing flow rate and soft stirring time in the process of detecting the molten steel temperature, chemical components and their contents, the process of adding the alloy and introducing the carbon wire, the process of melting the slag by applying electricity, and the soft stirring process in the LF furnaces with furnace numbers (1) to (4). [Table 5]

[0042] Here, the alloy contains ferrosilicon, metallic manganese and ferrochrome, and the Al contents in the ferrosilicon, metallic manganese and ferrochrome are shown in Table 6. Also, the C content in the ferrochrome is ≦0.15%, and the N content in the low nitrogen carburizer is ≦0.015%. [Table 6]

[0043] The chemical composition of the silicon carbide is SiC≧99.3% by mass, and contains other unavoidable impurities. The chemical composition and mass percentage of the synthetic slag are shown in Table 7. [Table 7]

[0044] (3) Billet casting process The molten steel tapped in the refining process was transferred to the continuous casting platform and left to stand for more than 15 minutes. When pouring into the large ladle, blocking sand was introduced into the slag receiver, and the molten steel was poured protectively into the tundish to form a continuous cast billet.

[0045] Here, the ladle bottom bricks, molten pool bricks, and ladle mouth bricks are all made of magnesia carbon bricks, and the number of times they have been used does not exceed 35 to 45 times; the ladle slag line bricks and breathable bricks are made of magnesium-zirconium-carbon bricks, and the number of times they have been used does not exceed 15 to 25 times; the ladle long nozzle is a corundum long nozzle, and the inner wall of the long nozzle is coated with a SiO2 coating, and the SiO2 coating has a thickness of 3 to 8 mm; the stopping sand is silicon chrome stopping sand, the inner wall of the tundish is coated with a magnesium coating, the tundish weir is a magnesium-zirconium-carbon weir, and the tundish top nozzle and immersion nozzle are all made of magnesia carbon nozzles.

[0046] The Al2O3 contents in the ladle bottom bricks, molten pool bricks, ladle mouth bricks, slag line bricks, permeable bricks, the stop sand, the magnesium coating of the tundish, the weir, the top nozzle, and the submerged nozzle are shown in Table 8. [Table 8]

[0047] The molten steel samples from the tundish were scanned with a Zeiss scanning electron microscope to count inclusions >1 μm in size. Scan area 1000 mm 2 The Al2O3 content in the inclusions was measured to be ≦8.5%, no Al2O3, magnesia-alumina spinel inclusions larger than 5 μm were observed, and the density of Al2O3, magnesia-alumina spinel inclusions with sizes of 1 to 5 μm was ≦0.0004 pieces / mm 2 It was.

[0048] Example 2 (1) Primary smelting process in the furnace Smelting was carried out in a 100 t electric furnace. Table 9 shows the molten steel temperature, C content, and O content at the end of smelting in the electric furnaces with furnace numbers (1) to (4). [Table 9]

[0049] At the end of smelting, slag was stopped and steel was tapped. Before tapping, silicon carbide and 40-60% low nitrogen carburizer were laid in advance at the bottom of the ladle receiving the molten steel. Alloys were added sequentially during tapping to alloy the steel. All alloys were added by the time the steel reached 75%. When the steel reached 80%, the remaining 40-60% low nitrogen carburizer was added at a rate of 200-300 kg / min. After the low nitrogen carburizer was completely dissolved in the molten steel, tapping was stopped and silicon carbide was added to the slag surface of the ladle. Synthetic slag was added to make slag. The slag basicity of the ladle was ≦0.6. The amounts of silicon carbide laid at the bottom of the ladle, silicon carbide added to the slag surface of the ladle after tapping, and synthetic slag added in the electric furnaces with furnace numbers (1) to (4) are shown in Table 10. [Table 10]

[0050] The ladle bottom blowing was performed throughout the entire tapping process. Table 11 shows the flow rates of the ladle bottom blowing for the electric furnaces (1) to (4) at the beginning of tapping, during the alloying process, when 80% of the steel is tapped and the addition of the remaining 40 to 60% low-nitrogen carburizer begins, and when tapping is completed and silicon carbide and synthetic slag are added to the slag surface of the ladle to make slag. [Table 11]

[0051] (2) Refining process The molten steel that has undergone primary smelting in the furnace is transferred to the LF furnace for refining, and the chemical composition of the molten steel is, in mass percent, C 0.70-0.95%, Si 0.15-0.45%, Mn 0.25-0.80%, Cr 0.10-0.45%, P 0.01-0.015%, S 0.008-0.01%, Alt 0.0005-0.0008%, N 0.0019-0.0030%, O In order to satisfy the requirement that the composition of the molten steel is 0.0011-0.0020%, with the balance being Fe and other unavoidable impurities, the temperature, chemical composition and their contents of the molten steel were detected, and the above-mentioned alloy was added according to the detected chemical composition and their contents of the molten steel, carbon wire was introduced, lime, silicon carbide and synthetic slag were added and electricity was passed through to melt the slag, the temperature of the molten steel was adjusted to 1510-1535°C, and the slag components were adjusted to satisfy the requirements of CaO / SiO2=0.9-1.2, Al2O3≦5%, MgO 4-8%, [MnO+T.Fe] 2-5%, with the balance being other unavoidable impurities, and then the ladle bottom blowing was adjusted to soft stirring mode with a soft stirring time of >20 min, and steel was tapped. Here, the amounts of lime, silicon carbide, and synthetic slag added to the LF furnaces with furnace numbers (1) to (4) and the slag basicity of the slag in the ladle are shown in Table 12. [Table 12]

[0052] Table 13 shows the ladle bottom blowing flow rate and soft stirring time in the process of detecting the molten steel temperature, chemical components and their contents, the process of adding the alloy and introducing the carbon wire, the process of melting the slag by applying electricity, and the soft stirring process in the LF furnaces with furnace numbers (1) to (4). [Table 13]

[0053] Here, the alloy contains ferrosilicon, metallic manganese, and ferrochrome, and the Al contents in the ferrosilicon, metallic manganese, and ferrochrome are shown in Table 14. Also, the C content in the ferrochrome is ≦0.15%, and the N content in the low-nitrogen carburizer is ≦0.015%. [Table 14]

[0054] The chemical composition of the silicon carbide is SiC≧99.3% by mass, and contains other unavoidable impurities. The chemical composition and mass percentage of the synthetic slag are shown in Table 15. [Table 15]

[0055] (3) Billet casting process The molten steel tapped in the refining process was transferred to the continuous casting platform and left to stand for more than 15 minutes. When pouring into the large ladle, blocking sand was introduced into the slag receiver, and the molten steel was poured protectively into the tundish to form a continuous cast billet.

[0056] Here, the ladle bottom bricks, molten pool bricks, and ladle mouth bricks are all made of magnesia carbon bricks, and the number of times they have been used does not exceed 35 to 45 times; the ladle slag line bricks and breathable bricks are made of magnesium-zirconium-carbon bricks, and the number of times they have been used does not exceed 15 to 25 times; the ladle long nozzle is a corundum long nozzle, and the inner wall of the long nozzle is coated with a SiO2 coating, and the SiO2 coating has a thickness of 3 to 8 mm; the stopping sand is silicon chrome stopping sand, the inner wall of the tundish is coated with a magnesium coating, the tundish weir is a magnesium-zirconium-carbon weir, and the tundish top nozzle and immersion nozzle are all made of magnesia carbon nozzles.

[0057] The Al2O3 contents in the ladle bottom bricks, molten pool bricks, ladle mouth bricks, slag line bricks, permeable bricks, the stop sand, the magnesium coating of the tundish, the weir, the top nozzle, and the submerged nozzle are shown in Table 16. [Table 16]

[0058] The molten steel samples from the tundish were scanned with a Zeiss scanning electron microscope to count inclusions >1 μm in size. Scan area 1000 mm 2 The Al2O3 content in the inclusions is measured to be ≦10%, no Al2O3, magnesia-alumina spinel inclusions larger than 5 μm are observed, and the density of Al2O3, magnesia-alumina spinel inclusions with a size of 1 to 5 μm is ≦0.0005 pieces / mm 2 It was.

[0059] In addition, Fig. 5 shows the distribution of inclusions in a steel cord according to one embodiment of the present invention in a ternary phase diagram of the SiO2-MnO-Al2O3 system. By comparing Fig. 5 with Fig. 1, it is found that the inclusions in the steel cord of the present invention are mainly SiO2-MnO inclusions, and compared to steel cords manufactured by conventional manufacturing processes, the amount of brittle inclusions such as Al2O3 and magnesia-alumina spinel (MgO·Al2O3) is significantly reduced, thereby making it possible to significantly reduce the wire breakage rate during drawing due to brittle inclusions.

Claims

1. 1. A method for controlling brittle inclusions in a steel cord having chemical components in mass percent of 0.70-0.95% C, 0.15-0.45% Si, 0.25-0.80% Mn, 0.10-0.45% Cr, P≦0.015%, S≦0.01%, Alt≦0.0008%, N≦0.003%, O≦0.002%, and the balance being Fe and other unavoidable impurities, a primary smelting process in which molten steel is deoxidized and alloyed, 0.5-1 kg / t of silicon carbide and 40-60% low-nitrogen carburizer are laid at the bottom of the ladle that receives the molten steel before tapping, and alloys are added successively during tapping to alloy the steel, all of the alloy is added by the time the steel reaches 75%, and when the steel reaches 80%, the remaining 40-60% of the low-nitrogen carburizer begins to be added at a rate of 200-300 kg / min, and after the low-nitrogen carburizer has completely dissolved in the molten steel, tapping is stopped and 0.5-1 kg / t of silicon carbide is added to the slag surface of the ladle and 3-5 kg / t of synthetic slag is added to create slag; The molten steel that has been through the primary smelting in the furnace is transferred to an LF furnace for refining, and the temperature, chemical components and contents of the molten steel are detected in order to adjust the chemical composition of the molten steel so that it satisfies, in mass percent, C 0.70-0.95%, Si 0.15-0.45%, Mn 0.25-0.80%, Cr 0.10-0.45%, P≦0.015%, S≦0.01%, Alt≦0.0008%, N≦0.003%, O≦0.002%, with the balance being Fe and other unavoidable impurities. In accordance with the detected chemical components and contents of the molten steel, the alloy is added, carbon wire is introduced, lime, silicon carbide and synthetic slag are added and an electric current is applied to melt the slag, the temperature of the molten steel is adjusted to 1510-1535°C, and the slag components are adjusted to, in mass percent, CaO / SiO 2 =0.9~1.2, Al 2 O 3 ≦5%, MgO 4-8%, [MnO+T.Fe] 2-5%, and the balance being other unavoidable impurities, and then adjusting the ladle bottom blowing to a soft stirring mode, setting the soft stirring time to >20 min, and performing a refining process of tapping steel; a billet casting process in which the molten steel tapped in the refining process is transferred to a continuous casting platform and left to stand for 15 minutes or more, stopper sand is introduced into a slag receiver when pouring into a large ladle, and the molten steel is protectively poured into a tundish to form a continuous cast billet, in this order; the alloy contains ferrosilicon, metallic manganese and ferrochrome, the ferrosilicon has Al≦0.035%, the metallic manganese has Al≦0.015%, the ferrochrome has Al≦0.020% and C≦0.15%, and the low-nitrogen carburizer has N≦0.015%.

2. The bottom bricks of the ladle, the molten pool bricks, and the ladle mouth bricks are all made of magnesia carbon bricks. 2 O 3 ≦3%, the slag line bricks and the air permeable bricks of the ladle are made of magnesium-zirconium-carbon bricks, and the Al content of the magnesium-zirconium-carbon bricks is 2 O 3 ≦3%, and the long nozzle of the ladle is a corundum long nozzle, and the inner wall of the long nozzle is coated with SiO 2 2. The method for controlling brittle inclusions in steel cord according to claim 1, characterized in that a coating is applied.

3. The stopper sand is silicon chrome stopper sand, and the Al 2 O 3 2. The method for controlling brittle inclusions in a steel cord according to claim 1, characterized in that the content of brittle inclusions in the steel cord is ≦5%.

4. A magnesium coating is applied to the inner wall of the tundish, and Al in the magnesium coating 2 O 3 ≦2%, the dam of the tundish is a magnesium-zirconium-carbon dam, and the Al content in the magnesium-zirconium-carbon dam is 2 O 3 ≦5%, and the upper nozzle and the submerged nozzle of the tundish are both magnesia carbon nozzles, and the Al in the magnesia carbon nozzle 2 O 3 2. The method for controlling brittle inclusions in a steel cord according to claim 1, characterized in that the content of brittle inclusions in a steel cord is ≦5%.

5. 2. The method for controlling brittle inclusions in a steel cord according to claim 1, characterized in that the in-furnace primary smelting step is performed in a converter or an electric furnace, and the molten steel temperature at an end point of smelting is ≧1650° C., C ≧0.10%, and O ≦0.03%.

6. 2. The method for controlling brittle inclusions in a steel cord according to claim 1, wherein, in the in-furnace primary smelting process, the ladle bottom blowing flow rate is 100 to 200 NL / min during the initial stage of tapping and during alloying, the ladle bottom blowing flow rate is 600 to 800 NL / min during a process in which the remaining 40 to 60% of the low-nitrogen carburizer is started to be added when 80% of the steel has been tapped, and the ladle bottom blowing flow rate is 300 to 500 NL / min during a process in which silicon carbide and synthetic slag are added to the slag surface of the ladle after tapping is completed to produce slag.

7. 2. The method for controlling brittle inclusions in a steel cord according to claim 1, characterized in that, in the refining process, a ladle bottom blowing flow rate is 100 to 150 NL / min in a process of detecting the molten steel temperature, chemical components and their contents, a ladle bottom blowing flow rate is 300 to 400 NL / min in a process of adding the alloy and introducing carbon wire, a ladle bottom blowing flow rate is 200 to 300 NL / min in a process of melting the slag by passing current, and a ladle bottom blowing flow rate is 30 to 80 NL / min in a soft stirring process.

8. 2. The method for controlling brittle inclusions in a steel cord according to claim 1, wherein a slag basicity in a ladle is set to ≦0.6 from the end of tapping in the in-furnace primary smelting step until adjustment of chemical components of the molten steel is completed in the refining step, and 1 to 2 kg / t of lime, 1 to 1.5 kg / t of silicon carbide, and 8 to 15 kg / t of synthetic slag are added in the refining step so that the slag basicity in the ladle is 0.9 to 1.

2.

9. The chemical composition of the silicon carbide is, by mass percent, SiC≧99.3%, and other unavoidable impurities. The chemical composition of the synthetic slag is, by mass percent, CaO 35-45%, SiO 2 45-55%, MgO 3-8%, Al 2 O 3 2. The method for controlling brittle inclusions in steel cord according to claim 1, characterized in that the content of brittle inclusions in steel cord is ≦2%, and other unavoidable impurities.

10. In the billet casting process, Als in the molten steel in the tundish is ≦0.0005%, and Al in the inclusions in the molten steel is 2 O 3 The content of inclusions is ≦10%, and Al 2 O 3 Inclusions, magnesia-alumina spinel inclusions size <5 μm, Al size 1-5 μm 2 O 3 Density of inclusions and magnesia-alumina spinel inclusions ≦0.0005 pieces / mm 2 2. The method for controlling brittle inclusions in a steel cord according to claim 1, wherein

Citation Information

Patent Citations

  • External refining production method of steel wire rod for cutting diamond wires

    CN111041352A

  • Method for producing high carbon steel wire rod

    JP2002332517A

  • High-strength steel wire rod superior in cold drawability, and manufacturing method therefor

    JP2004211148A

  • Wire rod for ultrahigh-strength steel cord and manufacturing method therefor

    WO2021056633A1